Environment-friendly composite lubricant and preparation method thereof

By combining oleic amide, lauramide, tung oil and other ingredients with emulsifiers, defoamers, high-temperature resistant fillers and antioxidants, an environmentally friendly composite lubricant was prepared, which solved the problems of lubricant volatility, loss or oxidation at high temperatures, and achieved the effects of internal lubrication, external lubrication, high-temperature resistance and environmental protection.

CN119842434AActive Publication Date: 2025-04-18HUBEI BODA SPECIAL LUBRICANT CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510338967.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

Under high temperature conditions, existing lubricants are prone to evaporation, loss or oxidation, resulting in a reduced lubricating effect and may cause environmental harm.

Method used

An environmentally friendly composite lubricant is prepared by using oleic acid amide, lauramide, tung oil and other ingredients to distribute emulsifiers, defoaming agents, high-temperature resistant fillers and antioxidants, and an environmentally friendly composite lubricant is prepared by ultrasonic vibration and thermal ethanol dissolution to ensure that it has the advantages of internal lubrication, external lubrication, high-temperature resistance and environmental protection at high temperatures.

Benefits of technology

It is achieved that the lubricant is not easily volatile, lost or oxidized under high temperature conditions, maintains good lubricating effect, and is environmentally friendly and reduces the harm to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of lubricating compositions, and particularly discloses an environment-friendly composite lubricant and a preparation method thereof.The environment-friendly composite lubricant is prepared from 30-40 parts of oleamide, 10-20 parts of lauramide, 5-10 parts of tung oil, 10-18 parts of an emulsifier, 1-3 parts of a defoaming agent, 1-3 parts of high-temperature-resistant filler, 0.5-1 part of an antioxidant and 30-50 parts of water. The preparation method comprises the following steps: S1, weighing the oleamide, the tung oil, the emulsifier and the water, mixing, heating to 70-80 DEG C, then adding the high-temperature-resistant filler, and uniformly mixing and stirring to obtain a primary mixture; s2, adding lauramide into the primary mixture, heating to 105-110 DEG C, continuing to stir uniformly, finally cooling, adding a defoaming agent and an antioxidant, and mixing and stirring uniformly to obtain a finished product lubricant; and meanwhile, the lubricating oil has internal lubricating and external lubricating effects, and has the advantages of high temperature resistance and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lubricating compositions, and more specifically, to an environmentally friendly composite lubricant and a preparation method thereof. Background Art

[0002] Lubricant is a plastic additive, including internal lubricant and external lubricant. External lubricant mainly improves the friction between the plastic melt and the metal surface of the molding equipment, reduces the friction between the two, and makes the plastic parts easier to demold; internal lubricant plays a role in reducing the cohesive force between molecules inside the plastic melt, which can reduce the internal friction of the plastic melt, increase the melting rate and melt deformability of the plastic, reduce the melt viscosity and improve the plasticizing properties.

[0003] However, in some special plastic processing processes, molding is often required under high temperature conditions. External lubricants are easy to evaporate and lose under high temperature conditions, reducing the lubrication effect. High temperature can also easily cause the oil film formed by the external lubricant to rupture and lose the lubrication effect. Internal lubricants are prone to oxidation and degradation under high temperature conditions to generate harmful substances. If the harmful substances leak, they are likely to affect the soil, water bodies and ecosystems.

[0004] Therefore, how to prepare a new composite lubricant that has both internal and external lubrication effects and has the advantages of high temperature resistance and environmental protection is a problem to be solved. Summary of the invention

[0005] In order to prepare a new composite lubricant that has both internal and external lubrication effects and has the advantages of high temperature resistance and environmental protection, the present application provides an environmentally friendly composite lubricant and a preparation method thereof.

[0006] In the first aspect, the present application provides an environmentally friendly composite lubricant, which adopts the following technical solution: An environmentally friendly composite lubricant comprises the following raw materials in parts by weight: 30-40 parts of oleic acid amide, 10-20 parts of lauramide, 5-10 parts of tung oil, 10-18 parts of emulsifier, 1-3 parts of defoamer, 1-3 parts of high temperature resistant filler, 0.5-1 part of antioxidant and 30-50 parts of water.

[0007] By adopting the above technical scheme, oleamide, lauramide and tung oil are matched, and the amide groups in oleamide and lauramide interact with each other and are evenly distributed in the plastic molecules. Oleamide and lauramide penetrate into the ions of each layer of plastic resin and into the particles, thereby reducing the friction between plastics and the friction between plastics and processing equipment, so that the prepared lubricant has both internal and external lubrication effects; and oleamide, lauramide and tung oil can form a lubricating film on the surface of the plastic, further improving the external lubrication effect; at the same time, the polar groups in oleamide and lauramide can weaken the intermolecular forces of the melt, promote melt flow, reduce melt viscosity, and further improve the internal lubrication effect.

[0008] Lauramide, tung oil, high temperature resistant filler and antioxidant are matched together. The heat resistance of lauramide and tung oil, the high temperature resistance of the filler and the high temperature anti-oxidation effect are utilized to prevent the oil film of the lubricant from breaking and evaporating and dissipating. The environmental protection effect of oleamide and tung oil is combined to make the composite lubricant have the advantages of internal lubrication, external lubrication, high temperature resistance and environmental protection.

[0009] Preferably, the oleamide is prepared by the following method: Hot ethanol is added to the oleamide particles and stirred until the oleamide is completely dissolved to obtain a solution with a mass fraction of 2-7%, which is then subjected to ultrasonic oscillation for 5-10 minutes, and then a dopamine hydrochloride solution is added, wherein the mass ratio of the solution to the dopamine hydrochloride solution is 1:0.1-0.25. After the reaction, oleamide is obtained by separation and purification.

[0010] By adopting the above technical scheme, oleamide particles are dissolved in hot ethanol, and then ultrasonic vibration is performed to make the oleamide evenly dispersed, and it helps to break the chemical bonds, cooperate with the amino group of dopamine hydrochloride, and facilitate the attachment of the amino group to the surface of the oleamide molecule, thereby realizing amino group loading. The amino group loading of dopamine hydrochloride can further improve the high temperature resistance of oleamide, so that the problem of lubricant volatilization and loss is not easy to occur during the processing of plastics at higher temperatures, thereby ensuring that the lubricant still has good internal and external lubrication effects under high temperature processing conditions.

[0011] Preferably, the frequency of the ultrasonic oscillation treatment is 20-40 kHz, and the time is 5-10 min.

[0012] By adopting the above technical solution, the frequency and time of ultrasonic oscillation are limited, the amino group loading is guaranteed, and the structure of oleic acid amide is not easily excessively damaged, thereby improving the high temperature resistant lubricating effect of oleic acid amide.

[0013] Preferably, the dopamine hydrochloride solution is a hot ethanol solution of dopamine hydrochloride with a mass fraction of 1-5%.

[0014] By adopting the above technical scheme, dopamine hydrochloride is dissolved in hot ethanol. During the ultrasonic oscillation process, dopamine hydrochloride is evenly dispersed and contacts with the molecules of oleamide. The amino group of dopamine hydrochloride is used to facilitate contact with the amide group of oleamide, so that the amino group of dopamine hydrochloride is loaded on oleamide, thereby improving the high temperature resistant lubrication effect of oleamide.

[0015] Preferably, the lauramide is prepared from a lauramide melt and graphite nanosheets in a mass ratio of 1:0.05-0.15.

[0016] By adopting the above technical scheme, graphite nanosheets are evenly dispersed in the lauramide melt. By utilizing the layered structure of the graphite nanosheets, the lauramide attached to the surface of the graphite nanosheets has a larger specific surface area, which is convenient for uniform contact with the plastic molecules. The contact between the plastic molecules and the lauramide, utilizing the barrier effect of the layered structure and the lubricating effect of the graphite nanosheets themselves, can further weaken the interaction between the plastic molecules, reduce the viscosity of the plastic molecules, ensure the viscosity of the plastic melt, and improve the internal lubrication effect.

[0017] Lauramide and graphite nanosheets are combined, and the good heat resistance of graphite nanosheets is utilized, and the dispersion effect of lauramide in the graphite nanosheet layer structure is combined to further improve the high temperature resistance of lauramide. During the lubrication process, lauramide can still have a good lubrication effect at a higher heating temperature. Lauramide and graphite nanosheets are combined. When lauramide and oleamide form an oil film on the plastic surface, the layered structure of graphite nanosheets is utilized, and the high mechanical strength and stability of graphite nanosheets are combined to further improve the stability of the oil film, and the problem of oil film rupture is not likely to occur under high temperature processing conditions, thereby ensuring that the composite lubricant has a good high temperature lubrication effect.

[0018] Preferably, the graphite nanosheets are prepared by loading a polyethylene glycol solution on graphite nanosheet particles.

[0019] By adopting the above technical scheme, when graphite nanosheets are dispersed in the lauramide melt, the hydroxyl groups of the polyethylene glycol solution are loaded on the surface of the graphite nanosheet particles, and the hydroxyl groups of the polyethylene glycol are used to facilitate mutual connection with the amino groups of dopamine hydrochloride on oleamide, thereby realizing the connection between oleamide and lauramide. The oleamide and lauramide uniformly dispersed in the plastic molecules form a lubricating network, which reduces the intermolecular force of the plastic, improves fluidity, reduces melt viscosity, and improves the high-temperature resistant lubricating effect of the lubricant.

[0020] The polyethylene glycol hydroxyl groups attached to the surface of graphite nanosheets facilitate mutual adsorption and bonding with the amide groups of lauramide, further improving the connection effect between graphite nanosheets and lauramide, thereby improving the high-temperature resistant lubrication effect of lauramide, and ensuring that lauramide has good internal and external lubrication effects during high-temperature processing of plastic products.

[0021] Preferably, the high temperature resistant filler is made of hydroxyapatite whiskers, nano boron nitride and polyglutamic acid solution in a mass ratio of 1:1-2:0.5-1.

[0022] By adopting the above technical scheme, the polyglutamic acid solution is attached to the surface of hydroxyapatite whiskers and nano-boron nitride, and the amino and carboxyl groups in the polyglutamic acid on the surface of the hydroxyapatite whiskers and nano-boron nitride are utilized to improve the adsorption and connection effect between the high-temperature resistant filler and the amide groups in oleic acid amide and lauryl amide, thereby improving the lubrication effect of the lubrication network inside the plastic molecules and improving the internal lubrication effect of the composite lubricant; the traction effect of the hydroxyapatite whiskers and the loading effect of the nano-boron nitride are combined to further improve the stability of the oil film formed by the composite lubricant on the plastic surface, and the problem of high-temperature oil film rupture and damage is not likely to occur; at the same time, the hydroxyapatite whiskers and nano-boron nitride have good high-temperature resistance, which can further improve the stability of the oil film, thereby improving the external lubrication effect of the composite lubricant.

[0023] Preferably, the defoaming agent is polydimethylsiloxane.

[0024] By adopting the above technical solution, polydimethylsiloxane has a lower surface tension and can evenly penetrate between plastic molecules, reducing the surface tension of the foam liquid film, thereby accelerating the foam bursting. In addition, polydimethylsiloxane has stable chemical properties and good environmental protection effects, so that the composite lubricant has good lubrication and environmental protection effects.

[0025] Preferably, the antioxidant is antioxidant 1010.

[0026] By adopting the above technical solution, the antioxidant 1010 has good thermal stability. Even when processing plastics under high temperature conditions, the problem of lubricant loss due to high temperature is not likely to occur. It also has good antioxidant effect and can effectively prevent thermal oxidation of polymer materials, so that the finished composite lubricant has good stability under higher processing temperature conditions, thereby having a better high-temperature resistant lubrication effect.

[0027] In a second aspect, the present application provides a method for preparing an environmentally friendly composite lubricant, using the following technical solution: A method for preparing an environmentally friendly composite lubricant comprises the following steps: S1. Weigh oleic acid amide, tung oil, emulsifier and water, mix them, heat them to 70-80°C, then add high temperature resistant filler, mix and stir evenly to obtain a primary mixture; S2. Add lauramide to the initial mixture, raise the temperature to 105-110°C, continue to stir evenly, and finally cool down, add defoamer and antioxidant, mix and stir evenly to obtain a finished lubricant.

[0028] By adopting the above technical scheme, oleamide and tung oil are matched to ensure that oleamide and tung oil are in liquid state at 70-80°C, and then the high-temperature resistant filler is evenly dispersed, and the temperature in the initial mixture is increased to 105-110°C to ensure that the lauramide crystals are hot-melted. After uniform mixing, lauramide, oleamide and tung oil are evenly dispersed and bonded to the high-temperature resistant filler to form a lubricating network, which is evenly dispersed in the plastic molecules, thereby reducing the viscosity of the plastic melt and improving the internal lubrication effect. The lubricating network can form an evenly distributed oil film on the surface of the plastic molecules, and the oil film is connected with the high-temperature resistant filler, further improving the high-temperature resistant lubricating effect of the composite lubricant; in combination with an antioxidant, under high temperature conditions, the composite lubricant is not prone to oxidation, volatilization and other problems, thereby ensuring the high-temperature stability of the composite lubricant.

[0029] In summary, this application has the following beneficial effects: 1. Oleamide, lauramide and tung oil are matched, and the amide groups in oleamide and lauramide interact with each other and are evenly distributed in the plastic molecules. Oleamide and lauramide penetrate into the ions and particles of each layer of plastic resin to reduce the friction between plastics and between plastics and processing equipment, so that the prepared lubricant has both internal and external lubrication effects.

[0030] 2. Lauramide, tung oil, high temperature resistant filler and antioxidant are matched together. The heat resistance of lauramide and tung oil, the high temperature resistance of filler and the high temperature anti-oxidation effect are utilized to prevent the oil film of lubricant from breaking and evaporating and dissipating. The environmental protection effect of oleamide and tung oil is combined to make the composite lubricant have the advantages of internal lubrication, external lubrication, high temperature resistance and environmental protection. DETAILED DESCRIPTION

[0031] The present application is further described in detail below in conjunction with embodiments.

[0032] Preparation Example of Oleic Acid Amide

[0033] Among the following raw materials, dopamine hydrochloride was purchased from Hubei Yongkuo Technology Co., Ltd.; other raw materials were all commercially available.

[0034] Preparation Example 1: Oleic acid amide is prepared by the following method: Add hot ethanol at a temperature of 70°C to the oleamide particles and stir until the oleamide is completely dissolved. During this period, hot ethanol is continuously added, and the mass fraction of ethanol is 99% to obtain a 5% mass fraction solution, which is then subjected to ultrasonic oscillation treatment at a frequency of 30kHz for 8 minutes; then add 2kg of dopamine hydrochloride solution to 10kg of the solution, the dopamine hydrochloride solution is a 3% mass fraction dopamine hydrochloride hot ethanol solution, the temperature of the hot ethanol in the dopamine hydrochloride hot ethanol solution is 70°C, and the mass fraction of ethanol is 95%, maintain the reaction at 70°C with stirring for 20 minutes, and then return to room temperature to obtain a semi-finished product; the semi-finished product is distilled and purified to obtain oleamide.

[0035] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: Add hot ethanol at a temperature of 70°C to the oleamide particles and stir until the oleamide is completely dissolved. During this period, hot ethanol is continuously added, and the mass fraction of ethanol is 99% to obtain a 2% mass fraction solution, which is then subjected to ultrasonic oscillation treatment at a frequency of 20 kHz for 10 minutes; then add 1 kg of dopamine hydrochloride solution to 10 kg of the solution, the dopamine hydrochloride solution is a 1% mass fraction dopamine hydrochloride hot ethanol solution, the temperature of the hot ethanol in the dopamine hydrochloride hot ethanol solution is 70°C, and the mass fraction of ethanol is 95%, maintain the reaction at 70°C and stir for 20 minutes, and then return to room temperature to obtain a semi-finished product; the semi-finished product is distilled and purified to obtain oleamide.

[0036] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: Add hot ethanol at a temperature of 70°C to the oleamide particles and stir until the oleamide is completely dissolved. During this period, hot ethanol is continuously added, and the mass fraction of ethanol is 99% to obtain a dissolving solution with a mass fraction of 7%. Then, ultrasonic oscillation treatment is performed at a frequency of 40 kHz for 5 minutes. Then, 2.5 kg of dopamine hydrochloride solution is added to 10 kg of the dissolving solution. The dopamine hydrochloride solution is a 5% mass fraction dopamine hydrochloride hot ethanol solution. The temperature of the hot ethanol in the dopamine hydrochloride hot ethanol solution is 70°C, and the mass fraction of ethanol is 95%. The reaction is maintained at 70°C with stirring for 20 minutes, and then the temperature is returned to room temperature to obtain a semi-finished product. The semi-finished product is distilled and purified to obtain oleamide.

[0037] Preparation Example of Lauramide

[0038] The following raw materials are all commercially available.

[0039] Preparation Example 4: Lauramide was prepared by the following method: The lauramide particles are heated to 110°C to completely melt to obtain a lauramide melt; 1 kg of graphite nanosheet particles are placed in 5 kg of polyethylene glycol solution, and then ultrasonically dispersed for 5 minutes at 20 kHz, wherein the polyethylene glycol solution is a polyethylene glycol aqueous solution with a mass fraction of 2%, and the polyethylene glycol is polyethylene glycol 800, and then the excess polyethylene glycol solution is filtered out, and the graphite nanosheet particles are dried and dispersed until they do not stick to each other and agglomerate, thereby obtaining graphite nanosheets; 0.1 kg of graphite nanosheets were added to 1 kg of lauramide melt at a rate of 30 g / min. During the addition, the lauramide melt was stirred at a speed of 100 r / min. After the addition was completed, stirring was continued for 20 min. After being uniformly mixed, the mixture was cooled and dispersed to obtain lauramide.

[0040] Preparation Example 5: This preparation example differs from Preparation Example 4 in that: 0.05 kg of graphite nanosheets were added to 1 kg of lauramide melt at a rate of 30 g / min. During the addition, the lauramide melt was stirred at a speed of 100 r / min. After the addition was completed, stirring was continued for 20 min. After mixing evenly, the mixture was cooled and dispersed to obtain lauramide.

[0041] Preparation Example 6: This preparation example differs from Preparation Example 4 in that: 0.15 kg of graphite nanosheets were added to 1 kg of lauramide melt at a rate of 30 g / min. During the addition, the lauramide melt was stirred at a speed of 100 r / min. After the addition was completed, stirring was continued for 20 minutes. After mixing evenly, the mixture was cooled and dispersed to obtain lauramide.

[0042] Preparation example of high temperature resistant filler

[0043] The following raw materials are all commercially available.

[0044] Preparation Example 7: The high temperature resistant filler is prepared by the following method: 1 kg of hydroxyapatite whiskers and 1.5 kg of nano-boron nitride are mixed evenly to obtain a mixture, wherein the average length of the hydroxyapatite whiskers is 100 nm, and the average particle size of the nano-boron nitride is 10 nm; then 0.8 kg of polyglutamic acid solution is added, wherein the polyglutamic acid solution is a polyglutamic acid aqueous solution with a mass fraction of 2%, and the addition rate of the polyglutamic acid solution is 60 mL / min. During the adding process, the mixture is continuously stirred at a speed of 100 r / min. After being evenly mixed, it is dispersed, and the hydroxyapatite whiskers and nano-boron nitride do not stick to each other and agglomerate, thereby obtaining a finished high-temperature resistant filler.

[0045] Preparation Example 8: This preparation example differs from Preparation Example 7 in that: 1 kg of hydroxyapatite whiskers and 1 kg of nano-boron nitride are mixed evenly to obtain a mixture, wherein the average length of the hydroxyapatite whiskers is 100 nm, and the average particle size of the nano-boron nitride is 10 nm; then 0.5 kg of polyglutamic acid solution is added, wherein the polyglutamic acid solution is a polyglutamic acid aqueous solution with a mass fraction of 2%, and the addition rate of the polyglutamic acid solution is 60 mL / min. During the adding process, the mixture is continuously stirred at a speed of 100 r / min. After being evenly mixed, it is dispersed, and the hydroxyapatite whiskers and nano-boron nitride do not stick to each other and agglomerate, so as to obtain a finished high-temperature resistant filler.

[0046] Preparation Example 9: This preparation example differs from Preparation Example 7 in that: 1 kg of hydroxyapatite whiskers and 2 kg of nano-boron nitride are mixed evenly to obtain a mixture, wherein the average length of the hydroxyapatite whiskers is 100 nm, and the average particle size of the nano-boron nitride is 10 nm; then 1 kg of polyglutamic acid solution is added, wherein the polyglutamic acid solution is a polyglutamic acid aqueous solution with a mass fraction of 2%, and the addition rate of the polyglutamic acid solution is 60 mL / min. During the adding process, the mixture is continuously stirred at a speed of 100 r / min. After being evenly mixed, it is dispersed, and the hydroxyapatite whiskers and nano-boron nitride do not stick to each other and agglomerate, thereby obtaining a finished high-temperature resistant filler.

[0047] Example

[0048] Example 1: An environmentally friendly composite lubricant: 35kg of oleic acid amide, 15kg of lauramide, 8kg of tung oil, 14kg of emulsifier, 2kg of defoamer, 2kg of high temperature resistant filler, 1kg of antioxidant, and 40kg of water; oleic acid amide is selected from the oleic acid amide prepared in Preparation Example 1, lauramide is selected from the lauramide prepared in Preparation Example 4, the high temperature resistant filler is selected from the high temperature resistant filler prepared in Preparation Example 7, the emulsifier is Tween 80, the defoamer is polydimethylsiloxane, and the antioxidant is antioxidant 1010; The preparation method is as follows: S1. Weigh oleamide and tung oil, mix them, heat them to 75°C, then add high temperature resistant filler, mix and stir evenly to obtain a primary mixture; S2. Add lauramide to the initial mixture, raise the temperature to 110°C, continue to stir evenly, and finally cool down, add defoamer and antioxidant, mix and stir evenly to obtain a finished lubricant.

[0049] Embodiment 2: This embodiment differs from Embodiment 1 in that: 30kg of oleic acid amide, 10kg of lauramide, 5kg of tung oil, 10kg of emulsifier, 1kg of defoamer, 1kg of high temperature resistant filler, 0.5kg of antioxidant, and 30kg of water; oleic acid amide is selected from the oleic acid amide prepared in Preparation Example 2, lauramide is selected from the lauramide prepared in Preparation Example 5, the high temperature resistant filler is selected from the high temperature resistant filler prepared in Preparation Example 8, the emulsifier is Tween 80, the defoamer is polydimethylsiloxane, and the antioxidant is antioxidant 1010; The preparation method is as follows: S1. Weigh oleic acid amide, tung oil, emulsifier and water, mix them, heat them to 70° C., then add high temperature resistant filler, mix and stir evenly to obtain a primary mixture; S2. Add lauramide to the initial mixture, raise the temperature to 105°C, continue to stir evenly, and finally cool down, add defoamer and antioxidant, mix and stir evenly to obtain a finished lubricant.

[0050] Embodiment 3: This embodiment differs from Embodiment 1 in that: 40kg of oleic acid amide, 20kg of lauramide, 10kg of tung oil, 18kg of emulsifier, 3kg of defoamer, 3kg of high temperature resistant filler, 1kg of antioxidant, and 50kg of water; oleic acid amide is selected from the oleic acid amide prepared in Preparation Example 3, lauramide is selected from the lauramide prepared in Preparation Example 6, the high temperature resistant filler is selected from the high temperature resistant filler prepared in Preparation Example 9, the emulsifier is Tween 80, the defoamer is polydimethylsiloxane, and the antioxidant is antioxidant 1010; The preparation method is as follows: S1. Weigh oleamide, tung oil, emulsifier and water, mix them, heat them to 80° C., then add high temperature resistant filler, mix and stir evenly to obtain a primary mixture; S2. Add lauramide to the initial mixture, raise the temperature to 110°C, continue to stir evenly, and finally cool down, add defoamer and antioxidant, mix and stir evenly to obtain a finished lubricant.

[0051] Embodiment 4: This embodiment differs from Embodiment 1 in that: The oleic acid amide prepared in Preparation Example 1 was replaced by commercially available oleic acid amide of equal mass in the raw materials.

[0052] Embodiment 5: This embodiment differs from Embodiment 1 in that: The raw materials were replaced with commercially available lauramide of equal mass in place of the lauramide prepared in Preparation Example 4.

[0053] Embodiment 6: This embodiment differs from Embodiment 1 in that: During the preparation of lauramide in the raw material, the graphite nanosheets are replaced by graphite nanosheet particles of equal mass, that is, the graphite nanosheets are not treated with a polyethylene glycol solution.

[0054] Embodiment 7: This embodiment differs from Embodiment 1 in that: No polyglutamic acid solution was added during the preparation of the high temperature resistant filler.

[0055] Embodiment 8: This embodiment differs from Embodiment 1 in that: No hydroxyapatite whiskers were added during the preparation of the high temperature resistant filler.

[0056] Comparative Example

[0057] Comparative Example 1: The difference between this comparative example and Example 1 is that: No lauramide and tung oil are added to the raw materials.

[0058] Comparative Example 2: The difference between this comparative example and Example 1 is that: No high temperature resistant fillers and tung oil are added to the raw materials.

[0059] Performance testing 1. Internal lubrication effect detection

[0060] The composite lubricant was prepared by the methods of Examples 1-8 and Comparative Examples 1-2, respectively. During the melt extrusion of PVC, the composite lubricant was added to PVC at a ratio of 0.5%, and melt extruded through a single screw extruder. The temperatures were: 100° C. in zone 1, 150° C. in zone 2, 190° C. in zone 3, 170° C. in die head, and 40 r / min in rotation speed. The extrusion volume was recorded. A high extrusion volume indicated low viscosity, good fluidity, and good internal lubrication effect.

[0061] 2. External lubrication effect detection

[0062] The composite lubricant was prepared by the methods of Examples 1-8 and Comparative Examples 1-2, respectively. During the melt extrusion of PVC, the composite lubricant was added to PVC at a ratio of 0.5%, and melt extruded through a single screw extruder. The temperature was: 100°C in zone 1; 150°C in zone 2; 190°C in zone 3; 170°C in die head; the rotation speed was 40 r / min; the surface smoothness of the extrudate was recorded and scored, and the scoring criteria were as follows: high surface smoothness, no burrs, and no obvious pits 10 points → severe surface roughness, severe burrs, and severe pits 1 point; and the sum of the pit areas with a pit diameter greater than 1 mm per unit area was calculated.

[0063] Table 1 Performance test table (“ / ” in the table means that the corresponding embodiment did not test the item, so there is no data)

[0064] It can be seen from Examples 1-3 and Table 1 that the composite lubricant prepared in the present application has a high extrusion volume, and even when polyvinyl chloride is processed at a higher temperature, it still has a high extrusion volume, indicating that the composite lubricant can reduce the cohesion of plastic molecules, reduce melt viscosity, improve fluidity, and facilitate extrusion molding; and the area and surface roughness are small, and the smoothness score is high, indicating that the composite lubricant can form an oil film on the plastic surface, reduce the friction between the plastic and the machine, and improve the external lubrication effect. The finished composite lubricant has good internal and external lubrication effects, and has a good lubrication effect even at a higher temperature.

[0065] Combining Example 1 and Examples 4-8 and Table 1, it can be seen that the raw material of Example 4 is replaced with commercially available oleic acid amide of equal quality prepared in Preparation Example 1. Compared with Example 1, the extrusion amount of the composite lubricant prepared in Example 4 is lower than that in Example 1, the area and the fraction are greater than those in Example 1, indicating that the heat resistance of oleic acid amide can be improved by treating it with dopamine hydrochloride solution, and the external lubrication effect can be further improved by treating it with amino groups.

[0066] In Example 5, the lauramide prepared in Preparation Example 4 was replaced with commercially available lauramide of equal mass in the raw materials. Compared with Example 1, the extrusion amount of the composite lubricant prepared in Example 5 was lower than that in Example 1, the area and the fraction were greater than those in Example 1, and the lauramide was lower than those in Example 1 after being treated with graphite nanosheets. This indicates that after lauramide is treated with graphite nanosheets, not only the high temperature resistance effect can be improved, but also a stable oil film can be formed on the plastic surface, which is not prone to roughness and pits on the plastic surface due to high temperature processing, and the surface smoothness is relatively high.

[0067] During the preparation of lauramide in the raw materials of Example 6, graphite nanosheets are replaced with graphite nanosheet particles of equal mass. Compared with Example 1, the extrusion amount of the composite lubricant prepared in Example 6 is lower than that in Example 1, and the area and surface area are greater than those in Example 1. This indicates that the polyethylene glycol hydroxyl groups attached to the surface of the graphite nanosheets are convenient for mutual adsorption and bonding with the amide groups of lauramide and oleamide, thereby further improving the high-temperature resistant lubrication effect of the composite lubricant and ensuring that lauramide has better internal and external lubrication effects during high-temperature processing of plastic products.

[0068] In the preparation process of the high-temperature resistant filler in Example 7, no polyglutamic acid solution was added. Compared with Example 1, the extrusion amount of the composite lubricant prepared in Example 7 was lower than that in Example 1, and the area and surface area were greater than those in Example 1. This indicates that the amino and carboxyl groups in the polyglutamic acid on the surface of hydroxyapatite whiskers and nano-boron nitride improve the adsorption and connection effect between the high-temperature resistant filler and the amide groups in oleic acid amide and lauryl amide, improve the lubrication effect of the lubrication network inside the plastic molecules, and improve the lubrication effect of the composite lubricant.

[0069] No hydroxyapatite whiskers were added during the preparation of the high-temperature resistant filler in Example 8. Compared with Example 1, the extrusion amount of the composite lubricant prepared in Example 8 was lower than that in Example 1, and the area and surface area were greater than those in Example 1. This indicates that the traction effect of hydroxyapatite whiskers and the loading effect of nano-boron nitride further improve the stability of the oil film formed by the composite lubricant on the plastic surface, and the high-temperature oil film is less likely to rupture or be damaged, thereby improving the lubricating effect of the composite lubricant. At the same time, hydroxyapatite whiskers have good high-temperature resistance, which can further improve the stability of the oil film under high-temperature conditions, thereby improving the lubricating effect of the composite lubricant.

[0070] Combining Example 1 and Comparative Examples 1-2 and Table 1, it can be seen that lauramide and tung oil are not added to the raw materials of Comparative Example 1. Compared with Example 1, the extrusion amount of the composite lubricant prepared in Comparative Example 1 is lower than that in Example 1, the area and the fraction are greater than those in Example 1, and the fraction is lower than that in Example 1; this indicates that oleamide and lauramide are infiltrated into the ions between the layers of the plastic resin and into the particles, reducing the friction between the plastics and the friction between the plastics and the processing equipment, so that the prepared lubricant has both internal and external lubrication effects; and oleamide, lauramide and tung oil can form a lubricating film on the surface of the plastic, further improving the external lubrication effect.

[0071] No high-temperature resistant filler and tung oil were added to the raw materials of Comparative Example 2. Compared with Example 1, the extrusion amount of the composite lubricant prepared in Comparative Example 2 was lower than that in Example 1, the area and the fraction were greater than those in Example 1, and the score was lower than that in Example 1. This indicates that the high-temperature resistant filler and tung oil are combined to improve the high-temperature stability of the lubricant, and the surface is smooth, and it has better internal and external lubrication effects under high-temperature conditions of plastic processing.

[0072] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An environmentally friendly composite lubricant, characterized in that: The invention comprises the following raw materials in parts by weight: 30-40 parts of oleic acid amide, 10-20 parts of lauryl amide, 5-10 parts of tung oil, 20-35 parts of emulsifier, 1-3 parts of defoamer, 1-3 parts of high temperature resistant filler, 0.5-1 parts of antioxidant and 30-50 parts of water.

2. The environmentally friendly composite lubricant according to claim 1, characterized in that: The oleamide is prepared by the following method: Hot ethanol is added to the oleamide particles and stirred until the oleamide is completely dissolved to obtain a solution with a mass fraction of 2-7%, which is then subjected to ultrasonic oscillation for 5-10 minutes, and then a dopamine hydrochloride solution is added, wherein the mass ratio of the solution to the dopamine hydrochloride solution is 1:0.1-0.

25. After the reaction, oleamide is obtained by separation and purification.

3. The environmentally friendly composite lubricant according to claim 2, characterized in that: The frequency of the ultrasonic oscillation treatment is 20-40 kHz, and the time is 5-10 min.

4. The environmentally friendly composite lubricant according to claim 2, characterized in that: The dopamine hydrochloride solution is a dopamine hydrochloride hot ethanol solution with a mass fraction of 1-5%.

5. The environmentally friendly composite lubricant according to claim 1, characterized in that: The lauramide is prepared from a lauramide melt and graphite nanosheets in a mass ratio of 1:0.05-0.

15.

6. The environmentally friendly composite lubricant according to claim 5, characterized in that: The graphite nanosheet is prepared by loading a polyethylene glycol solution on graphite nanosheet particles.

7. The environmentally friendly composite lubricant according to claim 1, characterized in that: The high temperature resistant filler is prepared from hydroxyapatite whisker, nano boron nitride and polyglutamic acid solution in a mass ratio of 1:1-2:0.5-1.

8. The environmentally friendly composite lubricant according to claim 1, characterized in that: The defoaming agent is polydimethylsiloxane.

9. The environmentally friendly composite lubricant according to claim 1, characterized in that: The antioxidant is antioxidant 1010.

10. The method for preparing an environmentally friendly composite lubricant according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh oleic acid amide, tung oil, emulsifier and water, mix them, heat them to 70-80°C, then add high temperature resistant filler, mix and stir evenly to obtain a primary mixture; S2. Add lauramide to the initial mixture, raise the temperature to 105-110°C, continue to stir evenly, and finally cool down, add defoamer and antioxidant, mix and stir evenly to obtain a finished lubricant.

Citation Information

Patent Citations

  • Water-soluble stamping and drawing lubricant and preparation method thereof

    CN111876226A

  • PVDF water-based composite lubricant and preparation method thereof

    CN113293056A

  • Copper alloy cutting fluid and preparation method thereof

    CN118308159A

  • Additive composition comprising an amidized or imidized polymer

    US20100113315A1

  • Aqueous lubricants

    US3950258A